2020
DOI: 10.18517/ijaseit.10.4.4199
|View full text |Cite
|
Sign up to set email alerts
|

Peat Soil Improvement Method Using Woven Bamboo and Cerucuk

Abstract: Most of the land in South Sumatera is the problematic soil, one of that is peat. Peat has low soil bearing capacity, and it becomes a problem when construction is built. Before the installation process, it is necessary to handle that soil. Soil improvement that can be done on peat to increase the bearing capacity value is the reinforcement method or physical stabilization. The results of research on woven bamboo and cerucuk are used as reinforcement material, which is expected to be an alternative to improve s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…Reinforcement with gelam wood pile combined with 3 layers of woven bamboo itself was able to increase the bearing capacity of the soil up to almost 10 times the condition without woven bamboo reinforcement. This shows that the use of gelam wood pile, either with woven bamboo or not, is able to increase the bearing capacity of the foundation on peat soil [12].…”
Section: Resultsmentioning
confidence: 84%
“…Reinforcement with gelam wood pile combined with 3 layers of woven bamboo itself was able to increase the bearing capacity of the soil up to almost 10 times the condition without woven bamboo reinforcement. This shows that the use of gelam wood pile, either with woven bamboo or not, is able to increase the bearing capacity of the foundation on peat soil [12].…”
Section: Resultsmentioning
confidence: 84%
“…The techniques are based on peat depth categories. Some studies have shown that the researchers have highlighted several techniques such as excavating, replacement, sand drain, lightweight fills, and stone columns [10]. In the current situation where the population of residents is increasing every year, need constructions player to identify alternative ways, and proper methods are needed to avoid the instability of the foundation structure caused by peat settlement [11].…”
mentioning
confidence: 99%